Correlation between Albumin, Colon Leakage Score (CLS), and Anastomotic Leakage after Colorectal Cancer Resection - Reno Rudiman; Putie Hapsari; Novi Christina Indrajaya (Faculty of Medicine, Universitas Padjadjaran, 2022)
Anastomotic leakage is still the most undesirable complication of colorectal surgery. The reported incidence of anastomotic leakage after colorectal surgery varies from 1.8% to 15.9%. The impact of anastomotic leakage is increased morbidity, mortality (12–30%), length of stay, and cost of hospitalization; hence, this complication should be prevented as much as possible.Several studies have shown a correlation between low albumin levels and increased anastomotic leakage.The Colon Leakage Score (CLS) is a standard score for predicting anastomotic leakage, but this score does not include the albumin level as a parameter of anastomotic leakage despite the importance of the albumin level’s contribution on the anastomotic leakage. Therefore, this study sought to analyze the correlation between the albumin level, CLS, and the incidence of anastomotic leakage after anastomotic resection surgery in colorectal cancer (CRC) patients at Dr. Hasan Sadikin General Hospital Bandung, Indonesia. This study was a cross-sectional retrospective analytical study on medical records of CRC patients over the age of 18 who underwent intestinal anastomotic resection surgery between 2016–2020. There were thirty-two patients with colorectal cancer underwent anastomotic resection during the study period, with two patients experienced anastomotic leakage. Correlation analysis showed that the correlation coefficient for the albumin level and anastomotic leakage was 0.209, while the correlation coefficient between CLS and anastomotic leakage was 0.110. There is no correlation between albumin level, CLS, and the incidence of anastomotic leakage after anastomotic resection surgery in CRC patients treated at Dr. Hasan Sadikin General Hospital Bandung, Indonesia